Full Protection for Graphene‐Incorporated Micro‐/Nanocomposites Containing Ultra‐small Active Nanoparticles: the Best Li‐Storage Properties. (5th October 2015) - Hou, Bao‐Hua; Wu, Xing‐Long; Wang, Ying‐Ying; Lü, Hong‐Yan; Liu, Dai‐Huo; Sun, Hai‐Zhu; Zhang, Jing‐Ping; Guan, Hong‐Yu
Abstract : In recent years, graphene‐incorporated micro‐/nanocomposites represent one of the hottest developing directions for the composite materials. However, a large number of active nanoparticles (NPs) are still in the unprotected state in most constructed graphene‐containing designs, which will seriously impair the effects of the graphene additives. Here, a fully protected Fe3 O4 ‐based micro‐/nanocomposite (G/Fe3 O4 @C) is rationally developed by carbon‐boxing the common graphene/Fe3 O4 microparticulates (G/Fe3 O4 ). The processes and results of full protection are tracked in detail and characterized by X‐ray diffraction, X‐ray photoelectron spectroscopy, and nitrogen absorption–desorption isotherms, as well as scanning and transition electron microscopy. When used as the anode for lithium‐ion batteries, the fully protected G/Fe3 O4 @C exhibits the best lithium‐storage properties in terms of the highest rate capabilities and the longest cycle life compared to the common G/Fe3 O4 composites and commercial Fe3 O4 products. These much improved properties are mainly attributed to its novel structural features including complete protection of active Fe3 O4 nanoparticles by the surface carbon box, a robust conductive network composed of nitrogen‐doped graphene nanosheets, ultra‐small Fe3 O4 NPs of 4–5 nm, abundant mesopores to accommodate the volume variation during cycling, and micrometer‐sized secondary particles. Abstract : The full protection of all ultra‐small Fe3 O4 nanoparticles for a graphene‐incorporated composite is successfully achieved by a thin carbon box, which can significantly improve the electrochemical properties in terms of higher rate capabilities and longer cycle life compared to the common G/Fe3 O4 and commercial Fe3 O4 when used as the anode for lithium‐ion batteries.